Observed and Perceived Teaching Creativity of English Teachers - Didit Suasta Adijaya; Luh Putu Artini; Ni Nyoman Padmadewi (Universitas Pendidikan Ganesha, 2021)
Many teachers still use teacher-centered methods in the learning process to make students passive in learning. This study aimed to analyze the creativity of teachers' teaching and how teachers implement creativity in the classroom. This study used the Embedded mix method in which qualitative data will be more dominant while quantitative data will be used as support. The techniques used in collecting data were observation, interviews, and questionnaires. The instrument used in collecting data was a questionnaire. The results of this study indicate that teachers consider themselves creative in teaching in the classroom. Teachers were categorized as slightly creative in teaching creativity in the classroom. The differences that occur between teacher perceptions and implementation were observed in the classroom in one way. Teachers perceive that they were creative. On the other hand, their teaching mostly focuses on conventional media, offline learning, and monotonous media and learning activities.